Assessment of Genetic Diversity in Garden Pea (Pisum sativum L.) and Identification of Promising Lines for Hybridization - , Gautam Pratap Singh, Vijay Kumar Singh, Anand Kumar, Ajay Bhardwaj, Ankur Kumar Rai (Archives of Current Research International, 2024)
The current study is being conducted to understand the degree of genetic divergence in order to discover more diversified parents for pea genetic advancement. The creation of high yielding varieties with stable productivity, resistance to diseases and unfavorable environmental conditions, various maturing types, a high rate of organic matter accumulation during the early stages of growth, a sufficiently high intensity of photosynthesis, increases in protein content, essential amino acids, and favorable ratios among them are the most important tasks for pea breeding. The present investigation was carried out at vegetable research farm and laboratory works in the department of Horticulture (Vegetable and Floriculture), BAU, Sabour, Bhagalpur, Bihar during the Rabi season 2020-21. The genotype Kashi Mukti, Kashi Uday, Kashi Nandini and VM-11 of cluster II exhibited superiority for earliness in first flower, days to 50% flowering and days to first picking and significantly better performance as measured by the lowest cluster mean and a substantial improvement in performance while the genotype Haze-02 of cluster IV exhibited superiority for inter-nodal length , plant height , seeds per pod and total sugars (%) based on maximum cluster mean with significantly better performance. It is anticipated that progenies from such diversified crossings will exhibit a broad range of genetic diversity and more potential for transgressive segregant isolation in the later generations. Therefore, a multiple crossing program using these genotypes may be used to retrieve transgressive segregants.